2022
DOI: 10.3390/s22176632
|View full text |Cite
|
Sign up to set email alerts
|

Stochastic Recognition of Human Physical Activities via Augmented Feature Descriptors and Random Forest Model

Abstract: Human physical activity recognition from inertial sensors is shown to be a successful approach for monitoring elderly individuals and children in indoor and outdoor environments. As a result, researchers have shown significant interest in developing state-of-the-art machine learning methods capable of utilizing inertial sensor data and providing key decision support in different scenarios. This paper analyzes data-driven techniques for recognizing human daily living activities. Therefore, to improve the recogn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 57 publications
1
7
0
Order By: Relevance
“…On several online human activity recognition datasets, they achieved a classification accuracy of 98.36%. Tahir [15] combined data preprocessing techniques with the primary domain features of human activities, such as time, frequency, wavelet, and time-frequency features. They employed a random forest classifier to monitor human body activities.…”
Section: Related Workmentioning
confidence: 99%
See 2 more Smart Citations
“…On several online human activity recognition datasets, they achieved a classification accuracy of 98.36%. Tahir [15] combined data preprocessing techniques with the primary domain features of human activities, such as time, frequency, wavelet, and time-frequency features. They employed a random forest classifier to monitor human body activities.…”
Section: Related Workmentioning
confidence: 99%
“…Subsequently, Euler angles are computed based on the sampled frequency-processing sequence data, with compensation provided through gyroscope and accelerometer data (lines [3][4][5][6][7][8][9][10][11][12]. Following this, the Euler angle vector is transformed into a rotation matrix, and from there into a quaternion and Rodrigues parameters (lines [13][14][15]. Finally, the ultimate pose angles are calculated and displayed (lines [16][17][18][19].…”
Section: Attitude Angle Calculation Algorithm Designmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent results have shown that IMUs and machine learning classifiers are very effective in identifying activities in healthy controls [ 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 ]. The accuracies often rely on the number of IMUs used and their location, with the wrist, chest, ankle, and thigh commonly used.…”
Section: Introductionmentioning
confidence: 99%
“…The accuracies often rely on the number of IMUs used and their location, with the wrist, chest, ankle, and thigh commonly used. Accuracies higher than 90% are even possible from cell phone IMU data for detecting several classes of activities (i.e., walking, sitting, standing, jogging, upstairs, and downstairs) [ 46 ]. However, the detection of activities in patient populations is complicated by larger variability in movement patterns across the population.…”
Section: Introductionmentioning
confidence: 99%